2001 Directory computerized criminal justice information systems - Scherpenzeel, Richard (Publication series, 2000)
Dr Richard Scherpenzeel (Ministry of Justice, the Netherlands) is the long-term consultant of HEUNI and the United Nations programme on the computerization of the administration of criminal justice systems. In the course of his work, he has gathered extensive information on computerized criminal justice information systems around the world. The Directory provides information on already existing applications. The purpose of the Directory is to assist criminal justice managers in identifying applications that may, with the proper tailoring, fit their needs, or at least in identifying practitioners who have experience in their particular field. The present report is an update to the directory published in HEUNI publication series (no. 27), 1995.